Gender Equality In Women's Jurisprudence According To Husein Muhammad And Its Relevance To The Goals Of Islamic Religious Education - Fahrub, Abdul Wahab; Alhaa, Dewi; Achadi, Muhammad Wasith (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This research begins with the lack of public understanding of gender and gender equality. These opinions are found in several books by Husein Muhammad, causing gender injustice (marginalization, subordination, stereotypes, double burdens, and violence) which often afflicts women who become victims. This research discusses the concept of gender equality in women's fiqh according to Husein Muhammad and discussing the relevance of the concept of gender equality in women's fiqh to the objectives of Islamic religious education. This study aims to determine the concept of gender equality in women's fiqh according to Husein Muhammad and to determine the relevance of the concept of gender equality in women's fiqh to the goals of Islamic religious education. This research uses a type of research, character thought to study using library research. Data collection techniques in this study are documentation and interviews with figures. The data analysis used is content analysis. The results of this study are first: the concept of gender equality in women's fiqh according to Husein Muhammad is an idea or idea consisting of some knowledge, namely about gender understanding, gender bias and gender roles which always emphasizes that the need for a women's fiqh decision in a well-social reality, economics, and politics. Women's fiqh consists of women's fiqh in the household, women's fiqh in worship, women's fiqh in marriage, women's fiqh in family health and women's fiqh in politics. The concept of the paradigm of feminism according to Husein Muhammad is to use the idea of ​​tauhid in gender relations, the principles of maqasid syari'ah and the methodology of interpreting a gender perspective. Second: the relevance of the concept of gender equality in women's fiqh according to Husein Muhammad with the aim of Islamic religious education are: (a) a dimension of faith that is relevant to the idea of ​​tauhid of gender between men and women, (b) a dimension of that is relevant to that women play an active role in the mind intellectually, (c) the dimension of understanding that is relevant to that women be able to understand the meaning of gender and actualize it, (d) the dimensions of practice that are relevant to women be able to play an active role in the domestic and public sphere, and (e) the dimensions of appropriate values with the principles of maqasid syari’ah. Keywords: Gender Equality, Women's Fiqh, Religious Education